The constitutionality of death penalty in Nigeria - Ayeni, Augustine M. (African journal of law and criminology, 2015)
This paper discusses the constitutionality of death penalty in Nigeria. It examines death penalty and religious views by specifically focusing on the two principal religions prevalent in Nigeria – Islam and Christianity. It also briefly discusses death penalty and international law by making reference to some global jurisdictions and relying on important international human rights Instruments with relevant decided cases where necessary. It equally examines various countries that have abolished death penalty, citing dates of abolition respectively along with jurisdictions that still retain death penalty. It looks at sentences in various countries of the world including Nigeria between 2007 and 2012. It concludes with the suggestion among others that Nigeria should revisit the issue of death penalty with the aim of abolishing it as many other countries have done, more so as taking such step is imperative for her being a prominent member of the United Nations and as an aspirant of permanent membership of the United Nation’s security council and the African Union.